Analisis Ragam Motif Henna Pada Jasa Lukis Fuji Henna Berdasarkan Teori Estetika Sussane K Langer - Aneu Levani; Wan Ridwan Husen; Asep Wasta (Abstrak : Jurnal Kajian Ilmu seni, Media dan Desain, 2025)
The public's need to provide henna painting services is currently important, considering the high enthusiasm of brides for using henna painting, so that henna artist services have become a promising profession. Apart from the emergence of this henna painting service, every henna artist has innovated various motifs. The aim of this research is to determine the variety of henna motifs in Fuji Henna painting services in Cintaraja Village, Singaparna District, Tasikmalaya Regency. This research uses qualitative research methods with a descriptive approach. The focus of this research is to analyze the various henna motifs on Fuji Henna painting services using Susanne K. Langer's aesthetic theory. The data collection techniques used were observation, interviews and documentation. The results of the research show that the variety of henna motifs at Fuji Henna painting services totals 11 motifs, including: 1) 2 dome motifs, 2) mandala, 3) flower, 4) Indian, 5) Arabian, 6) Botanical, 7) Russian, 8 ) African, 9) geometric, 10) modern, and 11) floral. The hanging flower motif is a characteristic motif of Fuji Henna ownership, with the symbol of the jasmine flower. There are 8 henna elements in Fuji Henna including dots, lines, outlines, flowers, leaves, paisley, filler and additional ornaments.